2009
DOI: 10.1097/mca.0b013e32832a198b
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine improves endothelial function in patients with stable coronary artery disease

Abstract: Ranolazine improves endothelial function, asymmetric dimethylarginine, and C-reactive protein levels in a group of patients with stable CAD. Our results suggest a novel mechanism of action of ranolazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
0
32
1
1
Order By: Relevance
“…RH-PAT is a validated 32 method for non-invasively measuring endothelial function and has been used in trials of patients with advanced CAD to show changes in endothelial function with interventions such as enhanced external counterpulsation 42 and the administration of ranolazine. 43 It also provides its own distinct information regarding risk, and a low reactive hyperemia signal detected by RH-PAT is independently associated with higher adverse cardiac event rates. 44 The relationship between endothelial function measured in large conduit arteries versus small resistance vessels is complex and incompletely understood, and in some studies did not correlate well with each other.…”
Section: Study Limitationsmentioning
confidence: 99%
“…RH-PAT is a validated 32 method for non-invasively measuring endothelial function and has been used in trials of patients with advanced CAD to show changes in endothelial function with interventions such as enhanced external counterpulsation 42 and the administration of ranolazine. 43 It also provides its own distinct information regarding risk, and a low reactive hyperemia signal detected by RH-PAT is independently associated with higher adverse cardiac event rates. 44 The relationship between endothelial function measured in large conduit arteries versus small resistance vessels is complex and incompletely understood, and in some studies did not correlate well with each other.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Deshmukh et al [12] included 27 patients with stable coronary artery disease and similar clinical characteristic as the patients in our study. Treatment with ranolazine improved endothelial function measured with peripheral arterial tonometry, which is comparable with our method in patients with coronary artery disease [25].…”
mentioning
confidence: 87%
“…It is believed that most of its anti-ischemic effect is related to the inhibition of the late phase of the inward sodium current (late I Na) following cardiac depolarization [11]. Deshmukh et al [12] found that ranolazine improves endothelial function in patients with stable coronary artery disease. In patients with type 2 diabetes with no evidence of cardiovascular disease, ranolazine improves endothelium-dependent vasodilation of the brachial artery in 2 weeks time, but decreases to the baseline value after 1 week of placebo [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in humans also support the concept that ranolazine may be beneficial by improving coronary blood flow by either reducing compressive effects of ischemic contracture or by improving endothelial function, or both (22). A recent study of 27 patients with stable ischemic heart disease found that ranolazine 1,000 mg bid improves endothelial dysfunction compared with placebo, as assessed using reactive hyperemia peripheral arterial tonometry of the index finger (23). Furthermore, Venkataraman et al (24) observed that ranolazine, at a median dose of 1,000 mg bid in patients with stable ischemic heart disease, significantly improved myocardial perfusion in zones of myocardial ischemia during treadmill exercise using technetium99m sestamibi single-positron emission computed tomography imaging without affecting heart rate or blood pressure at rest or at peak exercise, in an open-label nonrandomized pilot study.…”
mentioning
confidence: 98%